Modulating the Gelling Behavior of Pea Protein (Pisum sativum) through Glutaminase Induced Deamidation - Moncada P., Virgyl G. (Zamorano: Escuela Agrícola Panamericana, 2025)
The rheological stability of pea protein products is often compromised during storage or thermal processing due to protein unfolding and aggregation. Enzymatic deamidation, which catalyzes the conversion of glutamine to glutamic acid, offers a strategy to modify the physicochemical properties of these proteins. This study assessed the effects of glutaminase PG-500 on the gelling properties of pea protein (Pisum sativum) by evaluating viscosity, surface hydrophobicity, particle size, zeta potential, and structural morphology. Four treatments (control, point zero two five, point ser five, point one PG-500) were tested, and data were analyzed using Origin software and a Completely Randomized Design, with significance determined via Fisher s LSD test (P < point zero five). Results showed a concentration-dependent increase in suspensions' viscosity, with point one percent PG-500 reaching point six Pa·s versus point three Pa·s for the control. The storage modulus (G') decreased, indicating a transition to a softer gel network, with a yielding point at eight percent strain before failure. Stress relaxation tests revealed faster relaxation and lower equilibrium stress in all the enzyme concentrations, suggesting a weaker gel matrix. Surface hydrophobicity and zeta potential increased, improving solubility, while particle size decreased, enhancing dispersion stability. SEM analysis revealed a less dense gel structure in treated samples. These findings demonstrate that PG-500-mediated deamidation enhances the functional properties of pea protein gels, improving their suitability for food applications while maintaining nutritional value.